Extracellular acidosis stimulates breast cancer cell motility through aryl hydrocarbon receptor and c‐src kinase activation. Issue 7 (17th May 2022) - Miret, Noelia V.; Zárate, Lorena V.; Erra Díaz, Fernando; Leguizamón, M. Agustina; Pontillo, Carolina A.; Chiappini, Florencia A.; Ceballos, Leandro; Geffner, Jorge; Randi, Andrea S.
Abstract: A reduction in extracellular pH (pHe) is a characteristic of most malignant tumors. The aryl hydrocarbon receptor (AhR) is a transcription factor localized in a cytosolic complex with c‐Src, which allows it to trigger nongenomic effects through c‐Src. Considering that the slightly acidic tumor microenvironment promotes breast cancer progression in a similar way to the AhR/c‐Src axis, our aim was to evaluate whether this pathway could be activated by low pHe. We examined the effect of pHe 6.5 on AhR/c‐Src axis using two breast cancer cell lines (MDA‐MB‐231 and LM3) and mammary epithelial cells (NMuMG) and found that acidosis increased c‐Src phosphorylation only in tumor cells. Moreover, the presence of AhR inhibitors prevented c‐Src activation. Low pHe reduced intracellular pH (pHi), while amiloride treatment, which is known to reduce pHi, induced c‐Src phosphorylation through AhR. Analyses were conducted on cell migration and metalloproteases (MMP)‐2 and ‐9 activities, with results showing an acidosis‐induced increase in MDA‐MB‐231 and LM3 cell migration and MMP‐9 activity, but no changes in NMuMG cells. Moreover, all these effects were blocked by AhR and c‐Src inhibitors. In conclusion, acidosis stimulates the AhR/c‐Src axis only in breast cancer cells, increasing cell migration and MMP‐9 activity. Although the AhR activation mechanism still remains elusive, a reduction in pHi may be thought to be involved. These findings suggest a critical role for the AhR/c‐Src axis in breast tumor progression stimulated by an acidic microenvironment.